Employment and training policy in the United States during the economic crisis - Christopher J. O'Leary; Randall W. Eberts (W.E. Upjohn Institute for Employment Research, 2009)
This paper examines labor market conditions and public employment policies in the United States during what some are calling the Great Recession. We document the dramatic labor market changes that rapidly unfolded when the rate of gross domestic product growth turned negative, from the end of 2007 through early 2009. The paper reviews the resulting stress on labor market support programs and the broad federal response. That response came through modifications to existing programs and the introduction of new mechanisms to help Americans cope with job loss and protracted unemployment. The particular focus is on federally supported public programs for occupational job skills training and temporary income replacement. We also discuss procedures for evaluating the effectiveness of public reemployment efforts, and adjustments to these programs that were adopted during the crisis.
Keywords: J65; J68; 330; job training; unemployment; unemployment insurance; employment policy; federal stimulus; American Recovery and Reinvestment Act; evaluation; performance measurement; net impacts; cream skimming; adjustment methodology